2021
DOI: 10.5219/1676
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of sustainable agriculture practices by citrus farmers and its determinants in the Jordan valley: the case of Northern Ghor

Abstract: The agricultural sector in the Jordan Valley plays an important role in the economic system and that the region is essentially Jordan's food basket. The adoption of sustainable agricultural practices is widely recognized as essential to ensure agricultural sustainability. This study analyzed factors influencing citrus farmer's adoption of sustainable agricultural practices (SAPs) in the Northern Ghor of Jordan valley. The study used a quantitative approach. Simple random sampling was adopted to select 115 farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The National Agricultural Research Center in Egypt, for example, employs almost 100,000 people, yet its extension services to help farmers are severely lacking (Keulertz and Woertz, 2015). Indeed, education is crucial for sustainable agricultural growth because it raises their knowledge, improves their skills and practices, changes their attitudes and encourages farmers to use proper strategies and technologies, such as doing postharvest operations for perishable products and boosting AVA (Ali et al, 2021;Alwedyan and Taani, 2021;Marenya et al, 2021;Zobeidi et al, 2021). In addition to farmers, food processors and retailers must be educated to provide high-valueadded products.…”
Section: Discussionmentioning
confidence: 99%
“…The National Agricultural Research Center in Egypt, for example, employs almost 100,000 people, yet its extension services to help farmers are severely lacking (Keulertz and Woertz, 2015). Indeed, education is crucial for sustainable agricultural growth because it raises their knowledge, improves their skills and practices, changes their attitudes and encourages farmers to use proper strategies and technologies, such as doing postharvest operations for perishable products and boosting AVA (Ali et al, 2021;Alwedyan and Taani, 2021;Marenya et al, 2021;Zobeidi et al, 2021). In addition to farmers, food processors and retailers must be educated to provide high-valueadded products.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates the result from [30], who revealed that sex was significantly correlated with farmers' adoption of sustainable agricultural practices in Ebonyi State. On the other hand, [7] found that farmers' age, farming experience, and education status were factors that affected citrus farmers' adoption of sustainable agriculture practices in the Northern Ghor of Jordan valley. Similarly, [17] found that education level, income from agriculture, farmer cooperative and credit were determinant factors in the adoption of most of the agricultural practices that were considered.…”
Section: Factors That Influence the Level Of Use Of Sustainable Pract...mentioning
confidence: 98%
“…As the world grapples with the need to balance food security, environmental conservation, and economic viability, sustainable agricultural practices have emerged as a focal point for researchers, policymakers, and practitioners alike [4]. This bibliometric analysis delves into the vast body of literature surrounding the impact of sustainable agricultural practices on the economic sustainability of farmers, offering a comprehensive overview of the existing scholarly landscape [5].…”
Section: Introductionmentioning
confidence: 99%